2007
DOI: 10.1016/j.bbadis.2007.02.011
|View full text |Cite
|
Sign up to set email alerts
|

The cellular prion protein (PrPC): Its physiological function and role in disease

Abstract: Prion diseases are caused by conversion of a normal cell-surface glycoprotein (PrP(C)) into a conformationally altered isoform (PrP(Sc)) that is infectious in the absence of nucleic acid. Although a great deal has been learned about PrP(Sc) and its role in prion propagation, much less is known about the physiological function of PrP(C). In this review, we will summarize some of the major proposed functions for PrP(C), including protection against apoptotic and oxidative stress, cellular uptake or binding of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
329
0
13

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 361 publications
(346 citation statements)
references
References 176 publications
(193 reference statements)
4
329
0
13
Order By: Relevance
“…In the CNS, it has been proposed that the prion protein (PrP), a plasma membrane-anchored protein that binds copper ions with high specificity, serves as a receptor for cellular uptake and/or efflux of copper (Ref. 6). The role of PrP in copper trafficking has been supported by the correlation between PrP expression levels and copper content of cells (Ref.…”
Section: Overview Of Copper Homeostasis In the Central Nervous Systemmentioning
confidence: 99%
“…In the CNS, it has been proposed that the prion protein (PrP), a plasma membrane-anchored protein that binds copper ions with high specificity, serves as a receptor for cellular uptake and/or efflux of copper (Ref. 6). The role of PrP in copper trafficking has been supported by the correlation between PrP expression levels and copper content of cells (Ref.…”
Section: Overview Of Copper Homeostasis In the Central Nervous Systemmentioning
confidence: 99%
“…Among the myriad of interactions described, Hsp60 (Edenhofer et al, 1996), STI1 (Zanata et al, 2002), Bcl-2 (Kurschner and Morgan, 1995), and Grb2 (Spielhaupter and Schatzl, 2001) have been proposed as PrP c ligands. However, only a small proportion of these related pathways are functional in a physiological context (see (Lee et al, 2003) or (Westergard et al, 2007) and (Linden et al, 2008) for reviews). Two in vitro studies demonstrate that PrP c binds to the laminin receptor 67K (Gauczynski et al, 2001) and the adhesion molecule N-CAM (Santuccione et al, 2005;Schmitt-Ulms et al, 2001), both transducing survival signals or promoting neurite outgrowth.…”
Section: Prp C Ligands and Intracellular Signalingmentioning
confidence: 99%
“…Furthermore, several in vitro studies have addressed PrP c -mediated signaling (see (Westergard et al, 2007) for review). In this sense, we would like to remark two sets of studies with opens the notion of PrP c as a signaling molecule.…”
Section: Prp C Ligands and Intracellular Signalingmentioning
confidence: 99%
“…5,6 Thus, the ability of PrP c to modulate cell signaling was proposed to mediate some of its biological effects. 2,3 Using the constantly renewing intestinal epithelium as a model, we demonstrated a dual localization of PrP c : i) in differentiated enterocytes, plasma membrane PrP c is addressed specifically toward sites of cell-cell contacts, and more precisely at desmosomes, [6][7][8] whereas ii) in dividing cells, it is targeted to the nucleus. 7,9 Intercellular adhesion is able to control cell fate, especially cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…2 Despite absence of any severe phenotype, thorough analyses of Prnp knockout mice demonstrated that PrP c participates to several specific functions in specialized tissues, such as neuroprotection, synaptic activity, olfaction, immune response, epithelial and endothelial barriers. 3,4 The molecular mechanisms underlying the large repertoire of PrP c functions is far from being totally elucidated but the identification of multiple interactors began to provide more comprehensive knowledge.…”
Section: Introductionmentioning
confidence: 99%